1993
DOI: 10.1103/physrevlett.70.849
|View full text |Cite
|
Sign up to set email alerts
|

Surface barrier resonances on a simple metal

Abstract: We demonstrate the existence of a surface resonance below the vacuum level of a simple metal surface. Theoretical modeling of new scanning tunneling spectroscopy (STS) data from Al(lll) shows that the mechanism for formation of this resonance is scattering from the bulk lattice. Correlation between the STS feature and structure seen in inverse photoemission (IPE) spectra from Al(lll) suggests that the IPE feature is ajso attributed to this surface resonance, rather than a previously proposed matrix element eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Previous inverse photoemission and 2PPE experiments of aluminum surfaces lacked the energy resolution to distinguish resonances beyond n ¼ 2. For Al (100), a peak 0.2-0.5 eV below vacuum level was observed by Veyan et al [24], somewhat weaker but similar to that reported earlier for Al(111) [25][26][27]. Tentatively, this feature has been interpreted in terms of the ðn ¼ 1Þ imagepotential resonance or the superposition of a broadened full series of resonances [17,28,29].…”
mentioning
confidence: 58%
“…Previous inverse photoemission and 2PPE experiments of aluminum surfaces lacked the energy resolution to distinguish resonances beyond n ¼ 2. For Al (100), a peak 0.2-0.5 eV below vacuum level was observed by Veyan et al [24], somewhat weaker but similar to that reported earlier for Al(111) [25][26][27]. Tentatively, this feature has been interpreted in terms of the ðn ¼ 1Þ imagepotential resonance or the superposition of a broadened full series of resonances [17,28,29].…”
mentioning
confidence: 58%
“…[7][8][9][10] IPI states are present in systems where a bulk band gap provides a barrier, trapping electrons in the image tail of the surface potential. If no gap is present at the IPI energies, an electron is not reflected completely at the bulk barrier, and hybridization with surface truncated bulk states becomes possible.…”
Section: Introductionmentioning
confidence: 99%
“…Image potential states are Rydberg series of bound states whose binding energy is given by E n = 0.85/n 2 eV, where n= 1, 2, 3,... and have been reported in many metal surfaces. 23,24,[30][31][32][33] They are pinned to the vacuum level (E vac ) and thus the energy of n= 1 image potential state is 0.85 eV below E vac . The work function of i-Al-Pd-Mn turns out to be 5± 0.15 eV, and the resulting E vac is shown by an arrow in Fig.…”
Section: Resultsmentioning
confidence: 99%